Gestão da informação e do conhecimento em núcleo de Economia Solidária - Pereira, Vinicius (Universidade Federal de São Carlos, 2023)
Solidarity Economy presents a new collective way of production and consumption through property and work reorganization, disrupting economic, social and cultural paradigms, aiming for better social welfare and sustainable development. In this context, solidarity economy incubators support these initiatives through actions such as consultancies and interventions, fomenting social innovation through knowledge use. In Information Science, such organizations are still under-explored, especially regarding how they manage their knowledge and information, and how the literature relates to their particular context. Therefore, this research aims to analyze the Information and Knowledge Management (KIM) of the Integrated Multidisciplinary Nucleus of Studies, Formation and Intervention in Solidarity Economy (NUMI-EcoSol) of the Universidade Federal de São Carlos (UFSCar) as a case study, which included direct observation, document analysis and semi-structured interviews. Results point toward a knowledge intensive KIM of emergent nature, in a multidisciplinary and dialogical environment, where the incubation method presents characteristics of a non-structured competitive intelligence. Decision making is processual and dialogical, where decision-making spaces are the main knowledge transfer opportunity, with descriptive meeting minutes as an information tool. The presence of self-management impacts the Nucleus’ information policy and culture, and also its information flow, distinguishing itself from other social organizations by including decentralized practices and information autonomy on an individual and collective level. The nucleus creates social innovations mainly through projects and knowledge networks, where knowledge coordination and use of organizational memory are fundamental for its success. Challenges are faced, such as: knowledge loss, caused by the staff turnover and loss of gatekeepers; the management of a self-managed repository, in terms of structure and its consequent impact on information and knowledge retrieval; and time management on decision-making spaces, negatively affecting knowledge sharing and leading to knowledge under-use. We indicate minor incremental innovations such as expanding the use of ICT, increasing the number of communication channels; using a method like Kanban for email circulation; and possibilities for a structured competitive intelligence (or a new cooperative intelligence). Complementing the analysis, a metadata header prototype to be used in the Nucleus documents is presented, along with its immediate and long term benefits. Lastly, research suggestions are made to go beyond this case study, expanding on more general questions discussed in this research findings, such as the potential for interorganizational KIM and the epistemological matters involving information and knowledge in solidarity economy networks.
Information and knowledge management in Solidarity Economy nucleus
Keywords: Gestão da informação; Gestão do conhecimento; Economia solidária; Inovação social; Information management; Knowledge management; Solidarity economy; Social innovation; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO